PENGARUH PENGETAHUAN DAN SIKAP REMAJA TERHADAP PENERAPAN GIZI SEIMBANG SELAMA MASA NEW NORMAL COVID-19 DI MA DDI ALLIRITENGAE MAROS - Asmi Ranti; St. Masithah; Suherman Suherman; Icha Dian Nurcahyani; Kurnia Yusuf (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Adolescence is an age that is vulnerable to nutrition because of its rapid growth and it takes enough energy to perform a variety of physical activities. In the new normal of Covid-19, it is very important for us to have to improve the immune system which is the body's defense force to fight bacteria, viruses, and disease-causing organisms that we may touch, consume and breathe every day. The purpose of this study is to find out if there is an influence of adolescent knowledge and attitudes on the application of balanced nutrition during the New Normal period of COVID-19 at MA DDI Alliritengae Maros. This type of research is Ex post Facto with quantitative approach, a sample of 65 students selected from a population of 183 students using the formula Sloving. The variables in this study are knowledge and nutritional attitudes balanced with data collection tools using questionnaires or questionnaires with multiple linear regression analysis. The results showed that there is an influence of nutritional knowledge on the application of balanced nutrition judging by the results (p